NAVIGATING THE FINANCIAL LANDSCAPE: UNRAVELING THE COMPLEXITIES OF SMES' ACCESS TO FINANCE - Idarni Harefa; Tri Hartati Sukartini Hulu; Nanny Artatina Bu’ulolo; Intan Permata Hati Hulu (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The study airms to address the gaps in the existing research ons investigate how individual financial constraints, such as high interest rates, extended loan processing times, and complex security requirements, directly impact the operational aspects of SMEs. The paper offers a focused investigation into a specific aspect of SMEs – the direct impact of individual financial constraints on their operations. By reading the entire paper, individuals stand to gain a thorough grasp of the research methodology, detailed findings, and the broader implications for SMEs, policymakers, and financial institutions. In conclusion, the future agendas for enhancing access to finance for Small and Medium Enterprises (SMEs) revolve around embracing digital transformation, establishing flexible regulatory frameworks, investing in capacity building, promoting inclusive financing models, fostering global collaboration, integrating sustainability into financial decisions, improving data accessibility and analytics, and planning for economic resilience. A collaborative effort involving policymakers, financial institutions, industry stakeholders, and SMEs is crucial to create a dynamic and supportive ecosystem that ensures the financial inclusivity and long-term success of SMEs in an ever- evolving economic landscape.